Health promotion interventions to improve oral health of adolescents: A systematic review and meta‐analysis. Issue 6 (7th August 2020) - Tsai, Carrie; Raphael, Sarah; Agnew, Caitlin; McDonald, Gordon; Irving, Michelle
Abstract: Objectives: To evaluate the effectiveness of health promotion interventions on oral health knowledge, behaviour and status of healthy adolescents. Methods: This review included randomized controlled trials (RCTs) of oral health promotion interventions targeting adolescents. Primary clinical outcomes (gingival health, plaque scores, caries) and secondary proxy outcomes were evaluated. Meta‐analysis of primary outcomes was conducted where possible, with subgroup analysis based on intervention (comprehensive health promotion and education‐only). Results: Thirty‐seven eligible publications reporting on 28 unique RCTs of oral health promotion interventions were included. Quality appraisal of studies ranged from 48% to 96%. Interventions reported ranged from single‐session interventions to community‐wide programmes, including clinical preventive procedures and take‐home products. Half used a health behaviour change theory to inform their intervention. The meta‐analysis pooling of results favoured the intervention over control for all clinical outcomes, except DMFS in the education‐only subgroup. Stronger intervention effects were seen in the comprehensive intervention subgroup than the education‐only subgroup for DMFS ( P  = .02). This effect was slight, but not as clear in all other clinical categories. The majority of studies reported improvements in oral health knowledge, attitudes and behaviours. More positive outcomes were found with longer programmes, especially for dental caries outcomes. Conclusions: Oral health promotion programmes targeting adolescents have the ability to improve clinical oral health outcomes in the short and long term. Programmes should use more behavioural theory‐based interactive and strategic methods, including self‐awareness and the use of the wider community and peers for oral health promotion activities over a longer intervention duration.